Gravity Wave‐Induced Ionospheric Irregularities in the Postsunset Equatorial Valley Region. Issue 11 (3rd November 2017) - Hysell, D. L.; Fritts, D. C.; Laughman, B.; Chau, J. L.
Abstract: Plasma irregularities in the postsunset equatorial valley region ionosphere are investigated experimentally and through numerical simulation. Coherent radar backscatter observed at the Jicamarca Radio Observatory shows two classes of irregularities in different altitude bands—one mainly below about 125 km and the other mainly above. Irregularities in both bands are organized into wavefronts with wavelengths of a few kilometers. However, only the irregularities in the high‐altitude band exhibit consistent propagation speeds and directions. Some previous observations of irregularities in the nighttime electrojet suggest that gravity waves may sometimes influence their morphology. The possibility that the valley region irregularities are also related to gravity waves (GWs) is therefore investigated numerically. A model of a GW packet propagating through a tidal wind field is used to drive another model which predicts the resulting ionospheric electrodynamics. The combined simulation shows that GWs can induce field‐aligned currents and excite resistive drift waves which could be responsible for the valley region irregularities in the high‐altitude band. The GWs also induce irregularities in the upper E region directly through simple dynamo action which subsequently deform under the influence of shear flow. This may explain the irregularities in the low‐altitude band. Key Points: A new class of ionospheric irregularities observed in postsunset equatorial valley region Gravity waves generate irregularities by dynamo action below 125 km Above 125 km, resistive drift waves also involved in irregularity generation